The complete chloroplast genome sequence of Cenchrus purpureus - Yang Wu; Hui Zhou (Mitochondrial DNA. Part B. Resources, 2019)
The complete chloroplast genome sequence of Cenchrus Purpureus, important silage in China, is presented in this article. The total genome size is 138,199 bp, containing a large single copy (LSC) region (81,161 bp) and a small single copy region (12,386 bp) which were separated by two inverted repeat (IRs) regions (22,326 bp). The overall GC contents of the plastid genome were 38.6%. In total, 136 unique genes were annotated and they were consisted of 87 protein-coding genes, 41 tRNA genes, and 8 rRNA genes. Twenty-four genes duplicated in the LSC and IR regions. Eighteen genes contained one or two introns.